The future : a novel - Alderman, Naomi (Simon & Schuster, 2023)
"The bestselling, award-winning author of The Power delivers a dazzling tour de force where a handful of friends plot a daring heist to save the world from the tech giants whose greed threatens life as we know it. When Martha Einkorn fled her father's isolated compound in Oregon, she never expected to find herself working for a powerful social media mogul hell-bent on controlling everything. Now, she's surrounded by mega-rich companies designing private weather, predictive analytics, and covert weaponry, while spouting technological prophecy. Martha may have left the cult, but if the apocalyptic warnings in her father's fox and rabbit sermon--once a parable to her--are starting to come true, how much future is actually left? Across the world, in a mall in Singapore, Lai Zhen, an internet-famous survivalist, flees from an assassin. She's cornered, desperate and--worst of all--might die without ever knowing what's going on. Suddenly, a remarkable piece of software appears on her phone telling her exactly how to escape. Who made it? What is it really for? And if those behind it can save her from danger, what do they want from her, and what else do they know about the future? Martha and Zhen's worlds are about to collide. An explosive chain of events is set in motion. While a few billionaires assured of their own safety lead the world to destruction, Martha's relentless drive and Zhen's insatiable curiosity could lead to something beautiful or the cataclysmic end of civilization. By turns thrilling, hilarious, tender, and always piercingly brilliant, The Future unfolds at a breakneck speed, highlighting how power corrupts the few who have it and what it means to stand up to them. The future is coming. The Future is here."--provided by publisher.